1975
DOI: 10.1037/h0076908
|View full text |Cite
|
Sign up to set email alerts
|

Employment test validation for minority and nonminority clerks with work sample criteria.

Abstract: Ten tests of intellectual ability and perceptual speed and accuracy were validated against specially developed clerical work samples with a newly hired sample of 143 blacks, 74 Spanish-sumamed, and 195 whites. Most validity coefficients were statistically significant, and in only 2 out of 36 comparisons were ethnic sample validity coefficients significantly different. A combination of four tests was significantly predictive of clerical proficiency for each ethnic sample and for the total combined sample. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g. Boehm, 1977;Field, Bayley, & Bayley, 1977;Gael, Grant, & Ritchie, 1975b;Grant & Bray, 1970;Schmidt, Berner, & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than that for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g. Boehm, 1977;Field, Bayley, & Bayley, 1977;Gael, Grant, & Ritchie, 1975b;Grant & Bray, 1970;Schmidt, Berner, & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than that for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…Studies used to assess differential prediction normally use a combination of ability tests, including not only cognitive ability, but also knowledge and special skills such as clerical speed and accuracy (e.g. Boehm, 1977;Field et al, 1977;Gael et al, 1975b;Grant & Bray, 1970;Schmidt et al, 1973). Therefore, these differential prediction studies cannot necessarily be generalized to characterize CATs exclusively.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…In fact, several studies carried out in the 1970s support the finding that minority groups are rated less highly on objective criterion measures (e.g. Campbell, Crooks, Mahoney and Rock 1973;Gael and Grant 1972;Gael, Grant and Richie 1975a, 1975b, cited in Schmidt 1993. This body of evidence has led Schmidt to conclude 'The cumulative research on test fairness shows that the average ability and cognitive skill differences between groups are directly reflected in job performance' (Schmidt 1993, p. 5).…”
Section: Review Of the Literaturementioning
confidence: 96%
“…Studies used to assess differential prediction normally use a combination of ability tests, including not only cognitive ability but knowledge and special skills such as clerical speed and accuracy (c.f., Boehm, 1977;Field, Bayley & Bayley, 1977;Grant & Bray, 1970;Gael, Grant & Ritchie, 1975b;Schmidt, Berner & Hunter, 1973). Therefore, these differential prediction studies cannot necessarily be generalized to characterize CATs exclusively.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%
“…The assumption, however, is that both Blacks and Whites are characterized by the same regression line. Although it has been found that the slopes of both the Black and White regression lines are often similar, they frequently have different intercepts (e.g., Boehm, 1977;Field, Bayley & Bayley, 1977;Grant & Bray, 1970;Gael, Grant & Ritchie, 1975b;Ruch, 1972, as cited in Arvey & Faley, 1988;Schmidt, Berner & Hunter, 1973). Furthermore, the intercept of the regression line for Blacks is frequently found to be lower than the regression line for Whites, indicating that the use of a common regression line would over-predict job performance for Blacks according to the Cleary rule.…”
Section: Past Research: Inadequate As a Test Of The Thorndike Modelmentioning
confidence: 99%